CHARISMA IN CHRISTIAN TRADITION - Lemwang Chuhwanglim (Prodi Studi Agama-agama Fakultas Ushuluddin dan Dakwah IAIN Kediri, 2019)
The term charisma had been used and continues to use by many people in different context. There is charismain social, political, sports, culture and other modern leadership who have made many great impacts in winningpeople’s minds and hearts. This paper aims to analyze the meaning of Charisma in the Christian tradition andhow it influences in society until today. In doing so the article aims to see both negative and positive aspects andinfluence of charisma in different Christian social context. Though the article may not give an absolute pictureof the Christian tradition charisma being understood among other Christian denominations, it gives people torevisit the origin of the term Charisma and its evolution in the New Testament by the Apostle Paul. Hence, thisarticle will analyze the meaning of Charisma in the Christian tradition and how it influences in Christian societyuntil today and the authority of God being interpreted by charismatic group within and outside the Church.